How interoperable and standardised should IoT market be: A policy discussion from an EU-centric point of view - Mehmet Bilal UNVER; Ayşem Diker VANBERG (International Telecommunications Society (ITS), 2016)
Internet of Things (IoT) depicts a world of networked smart objects, including cars, refrigerators, health care services, wearable devices, etc. which mark a distinctive revolution in digital world. In order for this revolution to realise a certain level of interoperability and standardisation needs to take place. European Commission's previous efforts as to achieving IoT interoperability ended up some recommendations as to industrial solutions including industrial and innovation policies as well as monitoring exercises. Notwithstanding the milestones taken so far, more collaboration and solid analytical approach is needed for a future-proof and scalable solution. This paper revisits the IoT interoperability considering the previously taken measures including ex ante measures, i.e. data portability and ex post interventions, i.e. Microsoft decision. Depending on and benefiting from these progresses, the prospective standardisation and interoperability efforts are suggested to be comprehensive and detailed enough. Particularly it is suggested that future IoT standards and reference frameworks need to embody the standards applicable to data portability that are expected to be adopted in near future. It is also found that as IoT settings vary significantly a comprehensive approach would respond more appropriately to differing market situations. Last but not the least, in case industrial efforts fail to find appropriate and fitting solutions, determination of technical and legal interoperability in IoT context would rather rely on the European Commission as lack of interoperability would cause significant losses in consumer welfare and innovation capacity of the EU.
Keywords: 330; Interoperability; Internet of Things; Standardisation; European Commission; Digital Single Market; Protocol Layering